2013
DOI: 10.4038/sljbmi.v4i1.5523
|View full text |Cite
|
Sign up to set email alerts
|

What makes medical students to say “yes” to e-learning?

Abstract: IntroductionWith exponential expansion of Information Technology, the field of medical education has embraced innovative electronic learning (e-learning) techniques. The objectives of this study were to assess the acceptance of an integrated e-learning activity by first year medical students and to explore the association between the pattern of computer usage and their perception of such an intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These findings were similar to the studies done by Yapa et al, Thomas et al, Silva et al, Visalam et al, Kumar et al in medical students in Tamil Nadu, India. 13,14,18,20,21 The present study showed that most of students perceived that elearning is comparable to other traditional methods for acquiring clinical skills similar to the study done by Gormley et al among medical students. 22 In this study there was significant gender difference regarding e-learning with males having more access to infrastructure like computers or laptops than females and females spending less time in hours per week online for learning purpose when compared to males.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings were similar to the studies done by Yapa et al, Thomas et al, Silva et al, Visalam et al, Kumar et al in medical students in Tamil Nadu, India. 13,14,18,20,21 The present study showed that most of students perceived that elearning is comparable to other traditional methods for acquiring clinical skills similar to the study done by Gormley et al among medical students. 22 In this study there was significant gender difference regarding e-learning with males having more access to infrastructure like computers or laptops than females and females spending less time in hours per week online for learning purpose when compared to males.…”
Section: Discussionsupporting
confidence: 86%
“…In the studies done by Yapa et al, Silva et al, Jawaid et al, regarding attitude towards e-learning among medical students, majority of the students had access to their own computers and had better internet facilities compared to the students in this study. [13][14][15] The study showed that only 30% agreed that they were satisfied with the available infrastructure in the institution. This identifies the need to build up infrastructure to increase accessibility and availability for the purpose of e-learning.…”
Section: Discussionmentioning
confidence: 99%
“…About 18 (34.62%) of medical students had access to their own laptops and 45 (86.54%) had access to their own Internet facility. In the studies done by Vadlamani et al, Yapa et al, Silva et al, Jawaid and Ashraf regarding KAP towards e-learning among medical students, majority of the students had access to their own laptops and had better Internet facilities compared to the students in this study [5,[12][13][14]. The study showed that a few of the students had access to the institutional Internet service, but majority of them i.e.…”
Section: Discussionmentioning
confidence: 50%
“…Findings of our study were similar to the findings of Silva et al who also reported that the students attain basic computer literacy during school education which is widely used and developed during the phases of medical curriculum. 6 Attitudes are probably most developed by human interaction although the principles on which they are based can be learned. In this study, the attitude of medical graduates towards e-leaning was assessed.…”
Section: Discussionmentioning
confidence: 99%